2020
DOI: 10.7150/jca.45553
|View full text |Cite
|
Sign up to set email alerts
|

The miR-370/UQCRC2 axis facilitates tumorigenesis by regulating epithelial-mesenchymal transition in Gastric Cancer

Abstract: Ubiquinol-cytochrome c reductase core protein 2 (UQCRC2) is an important mitochondrial complex III subunit. This study investigated the role of UQCRC2 in gastric cancer (GC) and its upstream regulatory microRNAs (miRNAs). UQCRC2 expression levels were lower in GC tissues than non-carcinoma tissues. Furthermore, UQCRC2 levels were negatively correlated with lymph node metastasis, relapse, and tumor grade. Bioinformatics analysis predicted UQCRC2 as the target gene for miR-370, and this was verified in luciferas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 22 publications
(23 reference statements)
1
12
0
Order By: Relevance
“…Our previous study revealed a weak presence of UQCRC2 in GC tissues, as evidenced by quantitative real-time polymerase chain reaction (qRT-PCR). We further confirmed the feasibility of using UQCRC2 as a stand-alone diagnostic biomarker for GC disease survival, wherein we found that the expression level of UQCRC2 showed a significant negative correlation with disease progression [ 14 ].…”
Section: Introductionsupporting
confidence: 65%
See 2 more Smart Citations
“…Our previous study revealed a weak presence of UQCRC2 in GC tissues, as evidenced by quantitative real-time polymerase chain reaction (qRT-PCR). We further confirmed the feasibility of using UQCRC2 as a stand-alone diagnostic biomarker for GC disease survival, wherein we found that the expression level of UQCRC2 showed a significant negative correlation with disease progression [ 14 ].…”
Section: Introductionsupporting
confidence: 65%
“…Using dual-luciferase reporter assays, we confirmed that miR-488 can directly target UQCRC2. In previous studies, we discovered that UQCRC2 expression remains substantially low in GC tissues and is correlated with a better prognosis in GC patients [ 14 ]. Here, we showed that UQCRC2 knockdown suppressed the hsa_circ_0000751-mediated action on the proliferation and invasion of GC cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…complex I [46] and the UQCRC2 (Cytochrome b-c1 complex subunit 2) subunit of complex III [47], whereas no changes were detected in the level of the SDBH (Succinate dehydrogenase [ubiquinone] iron-sulfur subunit) of complex II [48], the COX IV (Cytochrome c oxidase subunit 4 isoform 1) subunit of complex IV [49], and the F1-beta-subunit of the mitochondrial ATP synthase of complex V [50] (Fig. 4A).…”
Section: Sos1 Ablation Is Linked To Specific Alterations Of Components Of Mitochondrial Respiratory Complexes and Their Assembly In Supermentioning
confidence: 99%
“…In contrast, osteosarcoma cell proliferation can be enhanced via targeting of ubiquinol-cytochrome c reductase core protein 1 (UQCRC1) with miR-214-3p [ 239 ]. In gastric cancer, the miR-370/UQCRC2 axis positively regulates the epithelial-mesenchymal transition (EMT) signalling that affects tumour proliferation and metastasis [ 240 ]. However, there is still limited information on direct regulation of mitochondria-encoded proteins by mitomiRs in cancer.…”
Section: Mirna Regulation Of Mitochondrial Genesmentioning
confidence: 99%